2018
DOI: 10.1186/s12931-018-0774-3
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal fine particulate exposure associated with reduced childhood lung function and nasal epithelia GSTP1 hypermethylation: Sex-specific effects

Abstract: BackgroundIn utero exposure to particulate matter with an aerodynamic diameter of less than 2.5 μm (PM2.5) has been linked to child lung function. Overlapping evidence suggests that child sex and exposure timing may modify effects and associations may be mediated through glutathione S-transferase P1 (GSTP1) methylation.MethodsWe prospectively examined associations among prenatal PM2.5 exposure and child lung function and GSTP1 methylation in an urban pregnancy cohort study. We employed a validated satellite-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 57 publications
(62 reference statements)
2
22
1
Order By: Relevance
“…Oxidative stress induces adverse effects in tissues. The developing fetus is highly vulnerable to oxidative stress injury, as the immune system remains immature during the prenatal period (Lee A. G. et al, 2018). Free radicals and chemicals inhaled during MSE and maternal PM exposure can pass the blood-placental barrier to directly increase the level of oxidative stress in the offspring.…”
Section: The Role Of Oxidative Stress In the Development Of Asthma Inmentioning
confidence: 99%
“…Oxidative stress induces adverse effects in tissues. The developing fetus is highly vulnerable to oxidative stress injury, as the immune system remains immature during the prenatal period (Lee A. G. et al, 2018). Free radicals and chemicals inhaled during MSE and maternal PM exposure can pass the blood-placental barrier to directly increase the level of oxidative stress in the offspring.…”
Section: The Role Of Oxidative Stress In the Development Of Asthma Inmentioning
confidence: 99%
“…For example, in the present study, the time spent for outdoor exercise was significantly higher in males (7.9 ± 7.6 hours) than that in females (7.3 ± 7.9 hours), which, due to time‐activity patterns, may affect the lung function development. However, some other studies found that males were more vulnerable to environmental factors . Therefore, the effects of genders as a modifier on the association between home renovation exposure and lung function are still unclear, and further studies are required to determine the cause of such differences.…”
Section: Discussionmentioning
confidence: 97%
“…However, some other studies found that males were more vulnerable to environmental factors. [34][35][36] Therefore, the effects of genders as a modifier on the association between home renovation exposure and lung function are still unclear, and further studies are required to determine the cause of such differences.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kaushal et al reported that prenatal arsenic exposure leads to the changes of five CpGs methylation in cord blood which were in the pathways related to cardiovascular diseases; also, the changed DNA methylation was associated with low-density lipoprotein of the children at the age of 2 to 14 years [30]. Additionally, prenatal particulate matter (PM) 2.5 exposure was associated with hypermethylation of children’s nasal epithelia glutathione S-transferase P1 ( GSTP1 ) gene that is also inversely associated with reduced children’s lung function in early childhood [56]. Although these evidence may suggest potential epigenetic toxicity of environmental exposures on the health later in life, they are powerless to illustrate if the environmentally induced epigenetic changes early in life are stable and functional until the occurrence of health events later in life, and vice versa.…”
Section: Epigenetic Toxicitymentioning
confidence: 99%